Gambaran Profil Penderita Tuberkulosis Paru Di Rsup Dr Soeradji Tirtonegoro Klaten - Nuraini, Fitri, Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
DESCRIPTION OF PULMONARY TUBERCULOSIS PATIENT PROFILE IN Dr SOERADJI TIRTONEGORO HOSPITAL OF KLATEN Abstrack Tuberculosis is an infectious disease which is a public health problem in the world including Indonesia. In Indonesia TB is a leading cause of death and the top morbidity after upper respiratory tract infection. The development of tuberculosis cases with BTA positive continues to increase in Indonesia. Increased prevalence of tuberculosis patients in Dr Soeradji Tirtonegoro Hospital Of Klaten need to analyze the causes and prevention so the incidence is decreased. The purpose of this study is to knowing Description Of Pulmonary Tuberculosis Patient Profile In Dr Soeradji Tirtonegoro Hospital Of Klaten. This study was using descriptive analytic method with cross sectional design which aims to determine the factors that cause pulmonary TB. The sample are 96 respondents using non probability sampling with accidental sampling technique. The data was analyzed by frequency distribution. The study shows that tuberculosis patients are mostly males 56,2%,ages 41-60 years old are 26%, economic status are mostly with income less than a million are 60,4%, elementary school education level are 45,5%,and 58,3% have history of smoking. deficient Nutritional status with IMT <18,5 are 59,4%. Patients with tuberculosis earlier stated and there is a history of contact with Tuberculosis is 51.1% of respondents. Environment in patients with tuberculosis, among others that have ventilation mostly have more than 3 windows in one house are 61.4%, lighting of the house who are not good are 18.7%, the house with ground floor are 9.3%. and density residential are 19.7%. Conclusion of this research was the respondents largely productive age, male gender, low education levels, low economic status, low nutritional status, has history of contact with TB and have a history of smoking before. Keywords: Tuberculosis, tuberculosis risk factors, environmental factors of tuberculosis